Some bioecological data regarding Pomacea haustrum (Reeve, 1856) predator-competitor of intermediate hosts of Schistosoma mansoni Sambon, 1907 - Milward-de-Andrade, Roberto; Carvalho, Omar dos Santos; Guimarães, Carlos Tito (Revista de Saúde Pública, 1978)
Observations carried out in the laboratory and the field (Belo Horizonte, MG, Brazil) offered the following biological and ecological informations Pomacea haustrum (Reeve, 1853), mollusk pilid, predator and competitor of Schistosoma mansoni intermediary host.